ODESSA TELEVISION METEOR PATROL - Gorbanev, Y. M. (Одеські астрономічні публікації, 2009)
The historical information on the photographic meteor studies in Odessa is given. A modern observational complex – television meteor patrol for recording the meteor events occurred in the Earth’s atmosphere is presented. The meteor patrol instruments available and the observation methods are specified. The meteor database structure is analyzed; the statistics of meteor observations conducted from June, 2003, to December, 2010, is reported. The total number of meteor events recorded by television method using various instruments is 4276. The software package is developed including 12 programs that enable to carry out the whole cycle of processing the observation data: from preprocessing to obtaining of the orbital elements of the recorded meteor particles. The programs on the basic and non-basic observations made in Odessa and at the observation stations in Kryzhanovka village and on Snake Island are presented. We also discuss the principal tendencies in the meteor studies conducted at Odessa astronomical observatory on the basis of observation results obtained by the meteor patrol using the television method.